The Concept of Pain Inventory (COPI): Assessing a Child's Concept of Pain. Issue 12 (December 2020) - Pate, Joshua W.; Simons, Laura E.; Hancock, Mark J.; Hush, Julia M.; Noblet, Tim; Pounder, Meg; Pacey, Verity
Abstract : Objectives: Clinical guidelines recommend that health care providers assist children to understand their experience of persistent pain, with pain science education a key component of clinical management in pediatric pain clinics. Currently, no tool exists to assess a child's concept of pain. The aim of this study was to develop such a tool and to evaluate its psychometric properties. Methods: After a rigorous process to generate items, assess content validity, evaluate readability and understandability, and pretest items, a cohort of 124 children (aged 8 to 12 y) independently completed the measure on 2 occasions, along with additional measures of pain, function, and pain-related distress. Results: The resulting unidimensional 14-item Concept of Pain Inventory (COPI) had acceptable internal consistency (α= 0.78) and moderate test-retest reliability (intraclass correlation coefficient (3, 1) = 0.55; 95% CI, 0.37-0.68). Higher COPI scores reflect greater alignment with contemporary pain science. COPI scores were inversely correlated with pain intensity and functional disability, but unrelated to pain catastrophizing and pain-related fear. At 1 to 2 months' follow-up, baseline COPI scores were inversely correlated with clinical variables of functional disability and pain intensity. Discussion: These results support the COPI as a brief, psychometrically sound tool to assess a child's concept of pain. Clinically, this tool may facilitate individualized pain science education to target identified conceptual "gaps" or misconceptions and to evaluate the effectiveness of pain science education in children. Further research examining its efficacy and impact is warranted. Abstract : Supplemental Digital Content is available in the text.